Safety and neurological assessments after autologous transplantation of bone marrow mesenchymal stem cells in subjects with chronic spinal cord injury - Mendonça, Marcus Vinícius Pinheiro; Larocca, Ticiana Ferreira; de Freitas Souza, Bruno Solano; Villarreal, Cristiane Flora; Silva, Luiz Flávio Maia; Matos, André Costa; Novaes, Marco Antonio; Bahia, Cláudia Maria Pinheiro; de Oliveira Melo Martinez, Ana Carine; Kaneto, Carla Martins; Furtado, Sissi Brandão Carneiro; Sampaio, Geraldo Pedral; et al. (Stem cell research & therapy, 2014)
The administration of stem cells holds promise as a potential therapy for spinal cord injury (SCI). Mesenchymal stem cells have advantages for clinical applications, since they can be easily obtained, are suitable for autologous transplantation and have been previously shown to induce regeneration of the spinal cord in experimental settings. Here we evaluated the feasibility, safety and potential efficacy of autologous transplantation of mesenchymal stem cells in subjects with chronic complete SCI. We conducted a phase I, non-controlled study in 14 subjects of both genders aging between 18 to 65 years, with chronic traumatic SCI (>6 months), at thoracic or lumbar levels, classified as American Spinal Injury Association (ASIA) A - complete injury. Baseline somatosensory evoked potentials (SSEP), spinal magnetic resonance imaging (MRI) and urodynamics were assessed before and after treatment. Pain rating was performed using the McGill Pain Questionnaire and a visual analogue score scale. Bone marrow-derived mesenchymal stem cells were cultured and characterized by flow cytometry, cell differentiation assays and G-band karyotyping. Mesenchymal stem cells were injected directly into the lesion following laminectomy and durotomy. Cell transplantation was an overall safe and well-tolerated procedure. All subjects displayed variable improvements in tactile sensitivity and eight subjects developed lower limbs motor functional gains, principally in the hip flexors. Seven subjects presented sacral sparing and improved American Spinal Injury Association impairment scale (AIS) grades to B or C - incomplete injury. Nine subjects had improvements in urologic function. One subject presented changes in SSEP 3 and 6 months after mesenchymal stem cells transplantation. Statistically significant correlations between the improvements in neurological function and both injury size and level were found. Intralesional transplantation of autologous mesenchymal stem cells in subjects with chronic, complete spinal cord injury is safe, feasible, and may promote neurological improvements. ClinicalTrials.gov NCT01325103 - Registered 28 March 2011.